The Role of Lipid Peroxidation Products in the Development of Oral Sub Mucous Fibrosis- A Cross-Sectional Survey: Lipid Peroxidation in Oral Sub Mucous Fibrosis - Naeem, Nooria; Nasrullah, Chaman; Shakeel, Maria; Hafiz, Zobiah; Mukhtar, Sara; Nasreen, Maimoona (Pakistan Journal of Health Sciences, 2024)
Oral sub mucous fibrosis (OSMF) is a premalignant condition. Factors that cause OSMF are areca nut, nutritional deficiency and genetics. These factors produce free radicals which generate oxidative stress by damaging DNA, lipids and proteins. Levels of 4 hydroxynonenal (4HNE), 8-hydroxy-2-deoxy guanosine (8-OHdG), C reactive protein (CRP), and malondialdehyde (MDA) were raised due to oxidative DNA damage and lipid damage. Objective: To determine the levels of lipid peroxidation by-products such as MDA, 4HNE, 8-OHdG, and CRP in patients with OSMF. Methods: A cross-sectional comparative study was conducted at The University of Lahore from January 2020 to August 2021. Fifty OMSF cases and fifty healthy controls were recruited by using non-probability convenient sampling technique. Serum of participants was analyzed for lipid peroxidation byproducts by using ELISA kits. The results were analyzed by applying independent t-test in SPSS version 21.0. Results: The mean MDA levels in OSMF patients were (3.22 ± 1.265nmol/ml) as compared to those of control group (1.26 ± 0.568nmol/ml). Serum CRP levels were significantly raised (1.23 ± 0.124mg/l) in patients of OSMF as compared to those of control group (1.04 ± 0.0324mg/l). The levels of 4-HNE, 8-OHdG were recorded as significantly increased in OSMF (1.5 ± 0.965pg/ml and 1.9 ± 0.265pg/ml) as compared to the those of control group (0.72 ± 0.065pg/ml and 0.09564 ± 0.00058pg/ml). Conclusions: It was concluded that the levels of MDA, 4HNE, 8-OHdG, and CRP were increased significantly in patients with OSMF compared to healthy controls.